Anatomy of Humans in Relation to Diseases and “Totality of the Symptoms”. Does it Require Modification in the Light of Later Hahnemann? How and When? (Advancements in Homeopathic Research, 2022)
Now a days we get cancer and chronic cases of mixed varieties having all mixed signs and symptoms of Miasms and also due to drugs (Para. 41, 42), operative procedures, X-Ray, Radiation, Chemotherapy, Steroids and their side effects, pain killers and strong medications with suppression of symptoms etc, and so or hence we need a different or modified approach for the treatment may be for prolonging the life or palliation of patients sufferings leaving aside the curative or cure aspect in many patients. Virgin cases are few. When the original disease signs and symptoms are/were lost or forgotten during treatment and such cases come to Homoeopaths, what can we do? Is there any way(s)? How do we know that the patient is better or worse physiologically, clinically and pathologically (Para. 200)?
Keywords: Diseases; Virgin; medications; Symptoms